Endoscopic Endonasal Repair of Congenital Defects of the Anterior Skull Base: Developmental Considerations and Surgical Outcomes - Gump, William C. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Techniques of endoscopic endonasal surgery, initially developed primarily for intracranial neoplasms, have been adapted to treat a wide variety of pathologies previously addressed with open craniotomy including congenital and acquired defects of the anterior skull base. Congenital defects can lead to herniation of leptomeninges containing cerebrospinal fluid alone or with brain tissue. Specific types of encephalocele can be defined on the basis of the associated abnormal bony anatomy. Endoscopic endonasal surgery represents a relatively recent development in the treatment of these entities. Technical considerations include relatively younger age range of the patient population, dimensions of preexisting bony defect, volume of herniated meninges and brain tissue, and distorted anatomy from abnormal development of the affected craniofacial skeleton. Recent highly detailed anatomical studies have quantitatively verified the utility of endoscopic endonasal surgery in the pediatric population. Particular attention has been directed toward adequacy of nasoseptal flap reconstruction in pediatric patients. Several reports have described patients with encephalocele of the anterior cranial fossa successfully treated with endoscopic surgery. The literature on endoscopic repair of congenital encephalocele is reviewed. Outcomes have generally been reported as favorable, although long-term follow-up and systematic studies have not been pursued.
Keywords: encephalocele; endoscopic surgery; endonasal surgery